Recent onset pseudoseizures--clues to aetiology. - Binzer, M; Stone, J; Sharpe, M (2004)
PURPOSE: To examine associations of potentially aetiological significance for the development of pseudoseizures by comparing patients with recent onset pseudoseizures with patients with recent onset epilepsy. METHODS: A prospective study of consecutive patients with recent onset pseudoseizures and epilepsy presenting to two Swedish hospitals. Demographic characteristics, somatic symptoms, depression severity, personality disorder, potential childhood aetiological factors and recent life events were elicited from clinical data and a research interview, which included a structured clinical interview for DSM-IV, a measure of perceived parental care and a life events inventory. RESULTS: Twenty patients with pseudoseizures of duration less than 12 months (mean 5.4 months) were compared with 20 patients with recent onset epilepsy. There was no statistically significant difference in the rate of current psychiatric disorder. Patients with recent onset pseudoseizures were however more likely to have a borderline personality disorder (P<0.05), and to recollect less parental warmth and more paternal rejection (P=0.0001) in childhood. They had no more life events in the 3 months prior to onset but did report more when the whole year before onset was assessed (P<0.001). CONCLUSIONS: Perceived childhood neglect, borderline personality, and an excess of life events over the preceding year is associated with pseudoseizures of recent onset more than with epilepsy. The study was limited by the small sample size making type two errors likely. However, by selecting both cases and controls with recent onset symptoms, the potential bias of differing illness durations and complicating factors of chronicity that have affected previous studies was avoided.